Pengaruh kualitas sistem, kualitas informasi, dan kualitas layanan terhadap penggunaan sistem e-learning di program pascasarjana universitas mercu buana - K, Purwanto S; Pawirosumarto, Suharno (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to determine and analyze the use of e-learning system Master of Management Program. Population in this research is student of system e-learning system of Management Master Degree Program of 2014. The method in this research is quantitative research, done by using statistical procedure to draw conclusion or hypothesis testing. Analytical methods used GSCA (Generalized Structured Component Analysis). Stages of activities undertaken are: (1) designing structural models; (2) designing the measurement model; (3) construct path diagrams; (4) the conversion of path diagrams to the system of equations; (5) estimates; (6) evaluation of goodness of FIT; And (7) hypothesis testing. The result of the research shows that the quality of the system influences and signifies the usage, (2) the quality of the information influences and significant to the usage, and (3) the quality of service influences and significant to the usage.